Pengaruh Psychological Empowerment dan Kompetensi Teknis Terhadap Kinerja Pegawai - Walin Zakki Falah; Syamsul Alam; Hardiani Hardiani; Herman Sjahruddin (BISMA : Business and Management Journal, 2026)
Employee performance is one of the important factors that determine the success of an organization in achieving its stated goals. In government organizations, especially judicial institutions, optimal employee performance is needed to support the implementation of effective, transparent, and accountable legal services. Although employee performance at the Makassar High Court shows high achievements, efforts to maintain and improve performance still need to be carried out through various influencing factors, including psychological empowerment and technical competence possessed by employees. This study aims to determine the effect of psychological empowerment and technical competence on employee performance at the Makassar High Court. The type of research used is quantitative research by utilizing 92 employees as respondents. Data analysis used multiple linear regression with the help of the SPSS program version 27.0. The results of the study indicate that psychological empowerment is in a good category, but cannot improve employee performance to a higher level. Meanwhile, employees are proven to have high technical competence so that they support the creation of employee performance to a higher level.